2013
DOI: 10.1200/jco.2013.31.15_suppl.6092
|View full text |Cite
|
Sign up to set email alerts
|

Sequential TKI treatments for iodine-refractory differentiated thyroid carcinomas.

Abstract: 6092 Background: Tyrosine kinase inhibitors (TKI) are currently used to treat patients with advanced iodine-refractory differentiated thyroid cancers (DTC) but none has been approved by the FDA or the EMA until now. Sometimes, patients are treated with off-label TKI when a clinical trial is not available or in second- and third-line therapy. Methods: We hereby report the efficacy of “off-label” sorafenib and sunitinib treatments as first-, second- and third-line therapy in metastatic DTC patients from the Fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Several correlative studies reported BRAF and other mutational statuses of participants (Kloos et al, 18 Brose et al 27 ). Other correlative studies noted areas of specific responsiveness (de la Fouchardiere et al, 16 Marotta et al, 25 Cabanillas et al 28 ) with most significant responses noted in lungs, lymph nodes, and liver lesions.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…Several correlative studies reported BRAF and other mutational statuses of participants (Kloos et al, 18 Brose et al 27 ). Other correlative studies noted areas of specific responsiveness (de la Fouchardiere et al, 16 Marotta et al, 25 Cabanillas et al 28 ) with most significant responses noted in lungs, lymph nodes, and liver lesions.…”
Section: Resultsmentioning
confidence: 90%
“…The Phase III Brose et al 1 study evaluated 57% papillary thyroid cancer, 25% FTC, and 10% PD (see Table 1 ). All of the studies used a sorafenib dose schedule of 400 mg twice daily, with the exception of the Adili et al 13 abstract, which did not include dose; the combination studies (Hong et al, 14 Cabanillas et al 15 [see Table 3 ]); and the observational studies by de la Fouchardiere et al, 16 which did not include dose, and Chen et al, 17 which used 200 mg twice daily (see Table 2 ). PR rates varied from 15% (Kloos et al 18 ) to 38% (Keefe et al 19 ), while SD rates varied from 34% (Hoftijzer et al 20 ) to 68% (Ahmed et al 21 , 22 ) in the Phase II setting.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The diminished second-line efficacy in comparison to the front-line setting is expected and is consistent with the experience of other cancer types for which therapeutic efficacy declines with an increasing number of prior lines of therapy [22][23][24]. A recent study reported comparable efficacy of second-line and first-line multiple kinase inhibitor therapy for differentiated thyroid cancer patients with a trend in favor of front-line therapy (median PFS: 6.7 month vs. 7.6 months; hazard ratio: 0.85 [95% CI: 0.45-1.61]; p ϭ .6) [25]. Interestingly, we observed efficacy diminution with the vascular-targeting class of agents, whereas treatment with nonantiangiogenic agents achieved comparable efficacy in the front-line and second-line settings.…”
Section: Discussionmentioning
confidence: 99%